Faculty perceptions of university-based transition services for students with intellectual disabilities in Saudi Arabia - Alhilfi, Reem Abdullah (Frontiers in Education, 2025)
This study explored faculty perceptions of university-based transition services for students with intellectual disabilities (IDs) in Saudi Arabia, using a descriptive analytical approach with a sample of 153 members. Faculty demonstrated strong competencies in transitional programs, particularly in philosophical foundations, program evaluation, educational content, and behavior management. This study emphasizes the importance of specialized training in postsecondary knowledge, collaboration, and assessment for special education teachers. No significant gender differences in faculty competency awareness were noted. The findings underscore the need for continuous faculty development, integrated curricula, and collaborative planning to enhance transitional programs in Saudi special education departments. Tailored educational content, student involvement, and guidance toward meaningful postsecondary pathways are recommended, focusing on holistic development, including social skills and family engagement.